Hodnocení toxicity hasebních vod - Rybková, Tereza (Vysoké učení technické v Brně. Fakulta chemická, 2010)
Problematika toxicity hasebních vod se v současné době dostává stále více do popředí zájmu. Při požáru dochází ke vzniku celé řady nebezpečných látek, které mohou negativně ovlivnit kvalitu některých složek životního prostředí. Cílem práce je posoudit ekotoxikologické vlastnosti hasebních vod, experimentální metodou určit toxicitu hasebních vod a přispět tak k prohloubení znalostí v doposud velmi málo řešené problematice.

The issue of toxic extinguishing water is currently getting more to the fore. When a fire arises a wide range of hazardous substances that may negatively affect the quality of some components of the environment. A significant problem can be then extinguishing water runoff into sewers or some components of the environment. The objective is to assess the ecotoxicological properties of extinguishing water, determine the toxicity of the extinguishing water by experiments and thus contribute to the deepening of knowledge in so very few solved problems.
Toxicity Assessment of Firewaters
Keywords: Testy toxicity; ekotoxikologie; hasební voda; hasební látky; pěnidla; Tests of toxicity; ecotoxicology; firewater; extinguishing agent; foaming agents